2006
DOI: 10.1111/j.1525-1438.2006.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic study of the putative precursor lesions of epithelial ovarian cancer in low-risk women

Abstract: Possible precursor lesions for epithelial ovarian cancer (EOC) have been defined in the ovaries of women with contralateral EOC, with breast cancer susceptibility gene (BRCA)-1 mutations, or with positive family history. We aimed to investigate the prevalence of these lesions in women without any recognizable risk and to correlate these lesions with clinical ovulatory markers. The study group consisted of 184 women who were operated for benign gynecological conditions. Patients were requested to fill a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In this study, we examined two sections per ovary and observed OEIs in 53% of women examined, which is similar to previous findings [31]. It has been reported that the incidence of OEIs increases with age [31, 32]. In this study, OEIs were more common in the ovaries of postmenopausal women (58%) than of premenopausal women (45%), but there was no trend of increasing numbers of OEIs with age in premenopausal women.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we examined two sections per ovary and observed OEIs in 53% of women examined, which is similar to previous findings [31]. It has been reported that the incidence of OEIs increases with age [31, 32]. In this study, OEIs were more common in the ovaries of postmenopausal women (58%) than of premenopausal women (45%), but there was no trend of increasing numbers of OEIs with age in premenopausal women.…”
Section: Discussionsupporting
confidence: 89%
“…Activation of this pathway may also repress expression of E-cadherin, a component of the epithelial cell tight junction that functions to establish and maintain cell polarity that is often altered in ovarian cancer cells to permit increased metastasis [43]. While no universally accepted precursor lesion exists for ovarian cancer originating in the OSE, menopausal ovaries and some mouse models of ovarian cancer exhibit hyperplasia of the OSE, formation of papillary structures, and inclusion cysts [44,45]. Insulin and IGF-I did not induce transformative changes in OSE as measured by growth in soft agar (data not shown); however, it is possible that if levels of insulin and IGF accumulate enough locally in disease they might act on early stages of ovarian cancer to increase proliferation and alter cell polarity to encourage hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…This statistical comparison with a control group is necessary because there is no threshold score for dysplasia. 24 For our study, we adopted and extended the score devised by Nieto et al We listed the cytological and architectural abnormalities that were most frequent and most representative of ovarian dysplasia after an exhaustive literature review (which also ensured excellent reproducibility and comparability for our study): ovarian dysplasia found in areas adjacent to stage 1 ovarian carcinoma, 21,25 in the controlateral ovary of women with stage 1 ovarian carcinoma, 26,27 in relation to ovulation induction, 22 and in prophylactic oophorectomy for BRCA mutation. 16,18,19 We incorporated all of these anomalies in order to have a complete dysplasia scoring system (Table 7).…”
Section: Discussionmentioning
confidence: 99%